Incidence And Prognostic Value Of Oral Candidiasis In Hiv Infection - Cristina Popa; Carmen Stelea; Eugenia Popescu (Romanian Society of Oral Rehabilitation, 2011)
Oral candidiasis is the most frequent lesion encountered in HIV infected patients and is detected before any other clinic symptoms of oral pathology. Its growth is a complex process of changes in the oral cavity, and sometimes disorders involving the entire body. Its risk is increased by serious factors as follows: autoimmune deficiencies (illness of the primary cells which acts as modulators of the immune response), xerostomia, malignant neoplasm, different therapies (chemotherapy, antibiotic therapy, therapy with steroids) or iron deficiency anaemia.